2017
DOI: 10.1159/000484078
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Clinical Evaluation of Data Logging in Cochlear Implant Recipients Using Automated Scene Classification Technologies

Abstract: Currently, there are no studies assessing everyday use of cochlear implant (CI) processors by recipients by means of objective tools. The Nucleus 6 sound processor features a data logging system capable of real-time recording of CI use in different acoustic environments and under various categories of loudness levels. In this study, we report data logged for the different scenes and different loudness levels of 1,366 CI patients, as recorded by SCAN. Monitoring device use in cochlear implant recipients of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
(13 reference statements)
7
9
0
Order By: Relevance
“…With regard to CI use, our data showed significant increases in device use across observations, but an average daily use that is still in line with previous studies (Busch et al, 2017;Cristofari et al, 2018). The increased use of CIs over the first year after implantation could be caused by a decrease in the hours that the children spent sleeping (Iglowstein et al, 2003) and by the parents' greater ability to help with CI use (Walker et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With regard to CI use, our data showed significant increases in device use across observations, but an average daily use that is still in line with previous studies (Busch et al, 2017;Cristofari et al, 2018). The increased use of CIs over the first year after implantation could be caused by a decrease in the hours that the children spent sleeping (Iglowstein et al, 2003) and by the parents' greater ability to help with CI use (Walker et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the authors found that the children with less exposure time to speech in quiet (at loudness levels lower than 70 dB) during interactions with others during the day had lower vocabulary scores. This is an important finding, given that, in previous research, speech in noise was found to be more frequent than speech in quiet in the auditory environments of cochlear-implanted children and adults (Busch et al, 2017), especially at younger ages due to their more frequent exposure to music (Cristofari et al, 2018;Rauch et al, 2019). However, early individual differences in vocabulary size may also have affected Guerzoni and Cuda's (2017) findings.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…As has been pointed out by [4], there have been no studies, to our knowledge, investigating the impact of CI and their relationship to complex social environments. Data logging may serve as an initial step by enabling comparison of different sound environments (scenes), especially quiet versus noise [15]. A further advantage of data logging is use time.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, we will evaluate the benefit of 3D volume rendering using the Nucleus audio processor equipped with a data recording system that can record in real time the use of CI in different acoustic environments and in various categories of volume levels [19]. Radiological evaluation plays a key role in CI surgery, but we must always keep in mind that temperament plays a role in the adaptation to CI and certain character traits may be risk or protective factors for surgery and rehabilitation outcomes [2022].…”
Section: Discussionmentioning
confidence: 99%